Pelatihan Ekonomi Digital Rumah Kreatif Pengrajin Sehati dalam Pemberdayaan UMKM Lokal di Desa Hulu Banyu Kandangan, Kabupaten Hulu Sungai Selatan - Harpriyanti, Haswinda; Hidayat, Muhammad; Kamariah, Kamariah (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The digital economy training organized for Sehati MSMEs in Hulu Banyu Kandangan, Hulu Sungai Selatan Regency, aims to empower MSME players to utilize digital technology to grow their businesses. The training consisted of two main sessions conducted over two weeks. In the first session, participants learned digital marketing strategies, while the second session focused on creating promotional media in the marketplace using the Canva application. Evaluation showed significant improvements in participants' technological knowledge and skills. A total of 20 participants successfully created digital content, managed social media accounts, and opened e-commerce accounts on platforms such as Shopee and Tokopedia. In addition, the service team also provided the UMKM Sehati website, two training modules, and a POS application to support daily business activities. Questionnaire results showed that 70% of participants felt more confident in using digital technology, and 65% rated the training facilities as very adequate. This training is expected to improve the competitiveness of local products and community welfare through digital technology-based MSME empowerment. Thus, this activity not only strengthens the local economy but also preserves local wisdom through technological innovation.